RNA interference in adult Ascaris suum – an opportunity for the development of a functional genomics platform that supports organism-, tissue- and cell-based biology in a nematode parasite. Issue 11 (September 2015) - McCoy, Ciaran J.; Warnock, Neil D.; Atkinson, Louise E.; Atcheson, Erwan; Martin, Richard J.; Robertson, Alan P.; Maule, Aaron G.; Marks, Nikki J.; Mousley, Angela
Graphical abstract: Highlights: RNA interference (RNAi) is readily achievable in adult Ascaris suum. RNAi is capable of spreading in adult A. suum. Multiple A. suum tissue-specific targets are susceptible to RNAi. Double-stranded RNA cocktails efficiently silence multiple targets simultaneously. RNAi is consistent across geographical isolates of A. suum . Abstract: The sustainable control of animal parasitic nematodes requires the development of efficient functional genomics platforms to facilitate target validation and enhance anthelmintic discovery. Unfortunately, the utility of RNA interference (RNAi) for the validation of novel drug targets in nematode parasites remains problematic. Ascaris suum is an important veterinary parasite and a zoonotic pathogen. Here we show that adult A. suum is RNAi competent, and highlight the induction, spread and consistency of RNAi across multiple tissue types. This platform provides a new opportunity to undertake whole organism-, tissue- and cell-level gene function studies to enhance target validation processes for nematode parasites of veterinary/medical significance.